2018
DOI: 10.1186/s13662-018-1808-3
|View full text |Cite
|
Sign up to set email alerts
|

Semianalytical solutions by homotopy analysis method for EIAV infection with stability analysis

Abstract: Equine Infectious Anemia Virus (EIAV) is a bovine lentivirus group that creates equine infectious anemia in horses around the globe. In this paper, we propose a basic nonlinear differential equation for EIAV infection. Moreover, we obtain a semianalytic approximate solution by the homotopy analysis method (HAM). The gain of this method allows providing a direct scheme for solving the problem. Furthermore, we find the local and global stability of disease-free and endemic equilibrium using a Lyapunov functional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…In this section, some definitions and properties of the fractional calculus and Sumudu transform are briefly mentioned. For more details see [14][15][16][17][18][19][20].…”
Section: Preliminaries and Notationsmentioning
confidence: 99%
“…In this section, some definitions and properties of the fractional calculus and Sumudu transform are briefly mentioned. For more details see [14][15][16][17][18][19][20].…”
Section: Preliminaries and Notationsmentioning
confidence: 99%
“…Previous modeling of EIAV analyzed virus and infected-cell dynamics with two viral strains and constant or decaying antibody levels [ 18 ], examined the protective effect of antibodies against multiple mutants [ 19 ], calculated quantitative kinetic estimates of antibody escape [ 20 ], showed that long-term dynamics depend on the ratio of cell-to-cell versus free-virus transmission [ 21 ] and calculated key kinetic parameters in the absence of adaptive immunity [ 22 ]. Other studies used EIAV as a case study to examine the mechanics of viral infection without cytopathicity [ 23 ], applied homotopy analysis to determine semi-analytical solutions [ 24 ], utilized global stability to estimate EIAV parameters [ 25 ], showed the existence of a Hopf bifurcation in a model of EIAV infection with a delay in the CTL response [ 26 ], and determined the number of vaccinations needed to prevent mutant escape [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Schwartz et al described infection in the context of sensitive or NAb-resistant strains, both in the presence of EIAV-specific antibodies [17] and with different modes of transmission [18], in order to better quantify lentivirus escape from antibody responses [19]. Geethamalini and Balamuralitharan studied a variety of theoretical models for EIAV and focused on mathematical analyses to determine semianalytical solutions and global stability of equilibria using homotopy analysis [20] to estimate parameters [21] and to show the existence of a Hopf bifurcation [22].…”
Section: Introductionmentioning
confidence: 99%